Answer:
The coefficient of a²b³c is -720
Step-by-step explanation:
Given: [tex](2a-b+3c)^6[/tex]
Let 2a-b = x and 3c = y
[tex](x+y)^6[/tex]
General term of binomial expansion.
where, n=6 , r=1 ( because exponent of c is 1)
[tex]\Rightarrow ^6C_1x^{6-1}y^1[/tex]
[tex]\Rightarrow 6(2a-b)^{5}3c[/tex] [tex]\because y=3c, x=2a-b[/tex]
[tex]\Rightarrow 18(2a-b)^{5}c[/tex] ----------(1)
Now, we simplify (2a-b)⁵
[tex]T_{r+1}=^5C_r(2a)^{5-r}(-b)^r[/tex]
The exponent of b is 3 and a is 2 .
If we take r=3 will get exponent of b is 3 and a is 2
So, put r=3
[tex]T_{4}=^5C_3(2a)^{2}(-b)^3=-40a^2b^3[/tex]
Substitute into equation (1)
[tex]\Rightarrow 18\cdot -40a^2b^3c[/tex]
[tex]\Rightarrow -720a^2b^3c[/tex]
Hence, The coefficient of a²b³c is -720